Évolution du jardin latin moderne », dans Du paradis au jardin latin - Nicolás Marías Rubió y Tudurí (Projets de Paysage)
The landscape architect Nicolás María Rubio y Tudurí is born in 1891 in Menorca. In Barcelona, where he studied, he met Jean-Claude Nicolas Forestier with whom he collaborated for the development of the gardens of Montjuic. He taught the art of gardening, from 1916 to 1924 at the Escola de Bells Oficis in Catalonia. In 1917, he was appointed director of public parks in Barcelona. Then, during the Second Republic, he became head of the department of urban planning of Catalonia. Little known in France, the work of Nicolás María Rubio y Tudurí is divided between architecture, parks design and writing. He published Del paraiso al jarding latino, vast synthesis of the history of gardens. He aims to show how the essence of Latin garden, or better, the garden of the Latin world developed through time and influenced all the other styles of design. In "Evolución del jardín latino moderno", last chapter of this book, he discusses the history of the gardens from the Italian Renaissance to modern times. We hope that the translation of this extract will contribute to increase awareness in France, on the work of this landscape architect and will not betray the lyricism of the Spanish text.